Efficacy and safety of targeted therapeutics for patients with radioiodine-refractory differentiated thyroid cancer: Systematic review and network meta-analysis - Ji, Xiaoyu; Liang, Weili; Lv, Guixu; Ding, Changyuan; Lai, Hong; Li, Luchuan; Zeng, Qingdong; Lv, Bin; Sheng, Lei (Frontiers in Pharmacology, 2022)
Background Multiple targeted therapeutics are available for radioiodine-refractory differentiated thyroid cancer (RAIR-DTC), but it remains unclear which treatment is optimal to achieve long-term survival. Methods A systematic search of the PubMed, Embase, and ClinicalTrials.gov databases was conducted to identify eligible randomized controlled trials (RCTs) comparing efficacy and safety of targeted treatments for patients with RAIR-DTC from inception to April, 2022. Data was extracted by following the recommendations of the Preferred Reporting Items for Systematic Review and Meta-analysis guideline. We calculated odds ratio (OR) or hazard ratio (HR), its corresponding 95% credible intervals (CrI), and the surface under the cumulative ranking curve (SUCRA) to indicate ranking probability using Bayesian network meta-analyses. The primary outcome was progression-free survival (PFS). The secondary outcomes were overall survival (OS), objective response rate (ORR), disease control rate (DCR), and grade 3 or higher adverse events. Results 12 eligible RCTs involved 1,959 patients and 13 treatments: apatinib, cabozantinib, anlotinib, nintedanib, lenvatinib, lenvatinib with low dose (LD), sorafenib, sorafenib plus everolimus, donafenib (200mg), donafenib (300mg), pazopanib (continuous), pazopanib (intermittent), and vandetanib. Pooled analyses indicated that targeted therapeutics significantly prolonged PFS and OS in patients with RAIR-DTC (0.31, 0.21–0.41; 0.69, 0.53-0.85, respectively) compared with placebo. Network meta-analyses indicated that lenvatinib showed the most favorable PFS, with significant differences versus sorafenib (0.33, 0.23-0.48), vandetanib (0.31, 0.20-0.49), nintedanib (0.30, 0.15-0.60), and placebo (0.19, 0.15-0.25), while apatinib was most likely to be ranked first for prolonging OS with a SUCRA of 0.90. Lenvatinib showed the highest ORR (66%, 61%-70%), followed by anlotinib (59%, 48%-70%) and apatinib (54%, 40%-69%). Lenvatinib caused the most adverse events of grade 3 or higher, followed by lenvatinib (LD) and apatinib. Different toxicity profiles of individual treatment were also revealed. Conclusion This network meta-analysis suggests that lenvatinib and apatinib were associated with the best progression-free survival and overall survival benefit respectively for patients with RAIR-DTC, compared with other targeted therapeutics. Patients who received lenvatinib or apatinib also had more grade 3 or higher adverse events.